Peningkatan Derajat Kesehatan Mental melalui Terapi Aktivitas Kelompok dalam Posyandu Jiwa - Desakmade Ari Dwijayanti; R. Tri Rahyuning Lestari; Ni Kadek Yuni Lestari; Ni Made Nopita Wati; I Gede Juana Masta (Jurnal Empathy Pengabdian Kepada Masyarakat, 2020)
Background: This community service activity aims to improve mental health by applying group activity therapy in the posyandu. Of the soul. Methods: Used is learning method by finding various information related to group activity therapy (TAK). The role play method is by practicing directly how the implementation of TAK is in accordance with their respective roles so that it can be demonstrated directly by the patient and what he wants to convey in the TAK can be properly addressed to the patient. Results: The problem faced at this time is the lack of community knowledge in this case the family in caring for people with mental disorders ODGJ and how treatment can be provided through TAK. Conclusions: Problem solving that can be done is to provide assistance in providing knowledge, understanding and implementing role play so that it can be applied in everyday life and improve mental health.